The Multimodal Construction of Brexit in the Economist (2017 – 2021) - Ishpekova–Bratanova, Kalina (Bulgarian Journal of International Economics and Politics, 2021)
This paper aims to show how and why the Economist constructs the post-Brexit European Union’s (EU) image in a string of commentaries published in the Charlemagne section in the 2017-2021 period. The theoretical concepts that provide the interdisciplinary methodological framework within which the research topic – the exposure of the discursive and cognitive mechanisms whereby the global media of British origin constructs the EU’s image and frames the debate about the EU – is explored encompass social semiotics and critical discourse analysis. The findings suggest that through its interplay of headline and subheading, together with the cartoon and textual body, the Economist holds the assumption that Brexit threatens the cohesion of the EU and prompts the drawing of a new balance of interests.